Population-Wide Peer Comparison Audit and Feedback to Reduce Antibiotic Initiation and Duration in Long-Term Care Facilities with Embedded Randomized Controlled Trial. (23rd March 2021) - Daneman, Nick; Lee, Samantha M; Bai, Heming; Bell, Chaim M; Bronskill, Susan E; Campitelli, Michael A; Dobell, Gail; Fu, Longdi; Garber, Gary; Ivers, Noah; Lam, Jonathan M C; Langford, Bradley J; et al.
Abstract: Background: Antibiotic overprescribing in long-term care settings is driven by prescriber preferences and is associated with preventable harms for residents. We aimed to determine whether peer comparison audit and feedback reporting for physicians reduces antibiotic overprescribing among residents. Methods: We employed a province wide, difference-in-differences study of antibiotic prescribing audit and feedback, with an embedded pragmatic randomized controlled trial (RCT) across all long-term care facilities in Ontario, Canada, in 2019. The study year included 1238 physicians caring for 96 185 residents. In total, 895 (72%) physicians received no feedback; 343 (28%) were enrolled to receive audit and feedback and randomized 1:1 to static or dynamic reports. The primary outcomes were proportion of residents initiated on an antibiotic and proportion of antibiotics prolonged beyond 7 days per quarter. Results: Among all residents, between the first quarter of 2018 and last quarter of 2019, there were temporal declines in antibiotic initiation (28.4% to 21.3%) and prolonged duration (34.4% to 29.0%). Difference-in-differences analysis confirmed that feedback was associated with a greater decline in prolonged antibiotics (adjusted difference −2.65%, 95% confidence interval [CI]: −4.93 to −.28%, P = .026), but there was no significant difference in antibiotic initiation. The reduction in antibiotic durations was associated with 335 912 fewer days of treatment. The embedded RCT detected no differences in outcomes between the dynamic and static reports. Conclusions: Peer comparison audit and feedback is a pragmatic intervention that can generate small relative reductions in the use of antibiotics for prolonged durations that translate to large reductions in antibiotic days of treatment across populations. Clinical Trials Registration . NCT03807466. Abstract : Audit and feedback with peer comparisons may not reduce antibiotic initiation in long-term care but is associated with small relative reductions in antibiotic treatment durations that translate to large population-wide reductions in antibiotic use.